Job Satisfaction as a Social Concern - Wiggins, Ronald L.; Steade, Richard D. (Academy of Management Review, 1976)
Individual and organizational adaptations to the dynamics of restricted economic growth are examined, and speculations are made about adaptations in a no-growth economy. The restricted-growth adaptations come together in job satisfaction, sought by the individual and provided by the organization in recognition of its social commitment.